A Questionnaire Based Study to Assess the Antimicrobial Stewardship Practices in the Tertiary Care Hospitals in India - Prashant Mishra; Harmanjot Singh Dhillon; Sandeep Vihan; Shashikant Bhargava (Research Center for Rational Use of Drugs (RCRUD), 2023)
Background: Due to emergence of antimicrobial-resistant healthcare associated infections (HAIs), the implementation of antimicrobial stewardship programs (AMSP) is the need of hour at institutional and national levels. We conducted an assessment of the current status of infrastructure, manpower, and education and training (E&T) in relation to Antimicrobial Stewardship (AMS) in the tertiary care hospitals of India. Methods: Healthcare professionals from 30 tertiary care hospitals in North-western India (public & private) were invited to participate in online survey from Nov 2022 to Apr 2023 by sending a pre-designed questionnaire about the current existing antimicrobial stewardship (AMS) practices at their hospitals through email. The answers received on various parameters of AMS were analyzed using descriptive statistics. Results: 72 healthcare professionals from 30 hospitals responded to the survey. 63% of the respondents had received education and training (E&T) on AMS during undergraduate or postgraduate training. 65% had not received any E&T at induction to the hospital. The positive responses were 36%, 47% and 33% for leadership support, accountability and availability of drug expertise in form of pharmacologist/pharmacist respectively. A policy to support optimal antibiotic use was present in 25% of respondents. Broad interventions to improve antibiotic use were scored as 28%, 7% and 6% for antibiotic time out, pre-authorization and prospective audit with feedback respectively. Conclusion: The findings reveal the enablers and barriers to implementation of antimicrobial stewardship and highlighted the need for establishing a framework for stricter implementation and monitoring of antimicrobial stewardship in Indian tertiary care hospitals. Few key areas which require immediate attention are: need for government level endorsement and leadership support of antimicrobial stewardship (AMS) activities; lack of AMS programs in hospitals; and lack of undergraduate/ postgraduate/at induction education and training in AMS for staff.